Growth Performance of Eucalyptus Clones in Saline Soils - Dhillon, Parmeet Singh; Dhillon, G. P. S.; Singh, Baljit (Indian Forester, 2019)
In a pot study conducted at Ludhiana, eight Eucalyptus clones (PE-11, C-2169, C-2013, C-2135, P-27, P-23, P-48 and C-405) were planted in three types of soils (S1-normal soil, S2-saline soil and S3-mixed soil). Observations on growth traits recorded at various ages exhibited significant differences among soil types as well as clones. S1 registered maximum plant height, collar diameter at all ages i.e. 45, 110 and 140 days after planting. Significantly lowest values were found in S2 (saline soil). S1 registered the maximum values for dry shoot and root biomass and the bottom rank was in case of S2. Clone PE-11 showed the maximum mean plant height, collar diameter at all three ages. The highest biomass of leaves and branches, stem and root were recorded by clone PE-11 under all soil types. The relative shoot and root biomass production in saline soils (S2) in comparison to normal soil was 25.8 and 28.9 per cent, 2 respectively. All the clones experienced reduction in biomass production, but relative values were highest in PE-11.